Face cooling with mist water increases cerebral blood flow during exercise: effect of changes in facial skin blood flow - Miyazawa, Taiki; Horiuchi, Masahiro; Ichikawa, Daisuke; Subudhi, Andrew; Sugawara, Jun; Ogoh, Shigehiko (Frontiers in Physiology, 2012)
Facial cooling (FC) increases cerebral blood flow (CBF) at rest and during exercise; however, the mechanism of this response remains unclear. The purpose of the present study was to test our hypothesis that FC causes facial vasoconstriction that diverts skin blood flow (SkBFface) towards the middle cerebral artery (MCA Vmean) at rest and to a greater extent during exercise. Nine healthy young subjects (20 ± 2 yrs.) underwent 3 minutes of FC by fanning and spraying the face with a mist of cold water ( 4˚C) at rest and during steady-state exercise (heart rate of 120 bpm). We focused on the difference between the averaged data acquired from 1 min immediately before FC and last 1 min of FC. SkBFface, MCA Vmean and MAP were higher during exercise than at rest. As hypothesized, FC decreased SkBFface at rest (-32 ± 4 %) and to a greater extent during exercise (-64 ± 10%, P=0.012). Although MCA Vmean was increased by FC (Rest, +1.4 ± 0.5 cm/s; Exercise, +1.4 ± 0.6 cm/s), the amount of the FC-evoked changes in MCA Vmean at rest and during exercise differed among subjects. In addition, changes in MCA Vmean with FC did not correlate with concomitant changes in SkBFface (r=0.095, P=0.709). MAP was also increased by FC (Rest, +6.2 ± 1.4 mmHg; Exercise, +4.2 ± 1.2 mmHg). These findings suggest that the FC induced increase in CBF during exercise could not be explained only by change in SkBFface.